Ответ:
1) (2; 5)
2) (4; -3)
3) (0; -6)
Объяснение:
1) ![\left \{ {{y = 3x - 1} \atop {2x + y = 9}} \right. \left \{ {{y = 3x - 1} \atop {2x + y = 9}} \right.](https://tex.z-dn.net/?f=%5Cleft%20%5C%7B%20%7B%7By%20%3D%203x%20-%201%7D%20%5Catop%20%7B2x%20%2B%20y%20%3D%209%7D%7D%20%5Cright.)
2x + (3x - 1) = 9
2x + 3x - 1 = 9
2x + 3x = 9 + 1
5x = 10
x = 10/5 = 2
y = 3x - 1 = 3 * 2 - 1 = 6 - 1 = 5
Ответ: (2; 5)
2) ![\left \{ {{4x + 5y = 1} \atop {8x - 2y = 38}} \right \left \{ {{4x + 5y = 1} \atop {8x - 2y = 38}} \right](https://tex.z-dn.net/?f=%5Cleft%20%5C%7B%20%7B%7B4x%20%2B%205y%20%3D%201%7D%20%5Catop%20%7B8x%20-%202y%20%3D%2038%7D%7D%20%5Cright)
![\left \{ {{4x + 5y = 1} \atop {4x - y = 19}} \right. \left \{ {{4x + 5y = 1} \atop {4x - y = 19}} \right.](https://tex.z-dn.net/?f=%5Cleft%20%5C%7B%20%7B%7B4x%20%2B%205y%20%3D%201%7D%20%5Catop%20%7B4x%20-%20y%20%3D%2019%7D%7D%20%5Cright.)
![\left \{ {{4x + 5y = 1} \atop {y = 4x - 19}} \right. \left \{ {{4x + 5y = 1} \atop {y = 4x - 19}} \right.](https://tex.z-dn.net/?f=%5Cleft%20%5C%7B%20%7B%7B4x%20%2B%205y%20%3D%201%7D%20%5Catop%20%7By%20%3D%204x%20-%2019%7D%7D%20%5Cright.)
4x + 5(4x - 19) = 1
4x + 20x - 95 = 1
4x + 20x = 1 + 95
24x = 96
x = 96/24 = 4
y = 4x - 19 = 4 * 4 - 19 = 16 - 19 = -3
Ответ: (4; -3)
3) ![\left \{ {{6 - 5(x - y) = 7x + 4y} \atop {3(x + 1) - 6x + 8y} = 69 + 3y} \right. \left \{ {{6 - 5(x - y) = 7x + 4y} \atop {3(x + 1) - 6x + 8y} = 69 + 3y} \right.](https://tex.z-dn.net/?f=%5Cleft%20%5C%7B%20%7B%7B6%20-%205%28x%20-%20y%29%20%3D%207x%20%2B%204y%7D%20%5Catop%20%7B3%28x%20%2B%201%29%20-%206x%20%2B%208y%7D%20%3D%2069%20%2B%203y%7D%20%5Cright.)
6 - 5(x - y) = 7x + 4y
6 - 5x + 5y = 7x + 4y
-5x + 5y - 7x - 4y = -6
-12x + y = -6
3(x + 1) - (6x + 8y) = 69 + 3y
3x + 3 - 6x - 8y = 69 + 3y
3x - 6x - 8y - 3y = 69 - 3
-3x - 11y = 66
![\left \{ {{-12x + y = -6} \atop {-3x - 11y = 66}} \right. \left \{ {{-12x + y = -6} \atop {-3x - 11y = 66}} \right.](https://tex.z-dn.net/?f=%5Cleft%20%5C%7B%20%7B%7B-12x%20%2B%20y%20%3D%20-6%7D%20%5Catop%20%7B-3x%20-%2011y%20%3D%2066%7D%7D%20%5Cright.)
![\left \{ {{y = -6 + 12x} \atop {-3x - 11y = 66}} \right. \left \{ {{y = -6 + 12x} \atop {-3x - 11y = 66}} \right.](https://tex.z-dn.net/?f=%5Cleft%20%5C%7B%20%7B%7By%20%3D%20-6%20%2B%2012x%7D%20%5Catop%20%7B-3x%20-%2011y%20%3D%2066%7D%7D%20%5Cright.)
-3x - 11(-6 + 12x) = 66
-3x + 66 - 132x = 66
-3x - 132x = 66 - 66
-135x = 0
x = 0
y = -6 + 12x = -6 + 12 * 0 = -6 + 0 = -6
Ответ: (0; -6)